2012
DOI: 10.1021/jp210953m
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Molecular Conformation, Packing, and Dynamics in Oligofluorenes: A Theoretical/Experimental Study

Abstract: Fluorene-based systems have shown great potential as components in organic electronics and optoelectronics (organic photovoltaics, OPVs, organic light emitting diodes, OLEDs, and organic transistors, OTFTs). These systems have drawn attention primarily because they exhibit strong blue emission associated with relatively good thermal stability. It is well-known that the electronic properties of polymers are directly related to the molecular conformations and chain packing of polymers. Here, we used three oligof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…3c). In contrast, a sharp small-angle reflection appears in the X-ray diffractogram of the pentafluorene film after annealing at 100 1C, which is likely related to crystallization, in agreement with previous results on bulk pentafluorene 31 and with the DSC trace. The completion of the cold crystallization process during annealing at 100 1C was finally confirmed with transmission diffraction experiments in temperature (Fig.…”
Section: Thermal and Structural Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…3c). In contrast, a sharp small-angle reflection appears in the X-ray diffractogram of the pentafluorene film after annealing at 100 1C, which is likely related to crystallization, in agreement with previous results on bulk pentafluorene 31 and with the DSC trace. The completion of the cold crystallization process during annealing at 100 1C was finally confirmed with transmission diffraction experiments in temperature (Fig.…”
Section: Thermal and Structural Propertiessupporting
confidence: 91%
“…A previous study has shown by a combination of DSC and solid-state NMR measurements that the oligofluorenes tend to adopt distinct molecular conformations according to the number of monomeric units. 31 A plausible explanation for our photophysical results is that the oligofluorenes of different lengths show various degrees of twisting between fluorene units in the solid-state and this could substantially affect the actual conjugation length of the molecules. Overall, our results suggest that the actual conjugation length is structurally dependent and, as a consequence, the oligomer chain length should be distinguished from the effective conjugation length in the oligofluorene films.…”
Section: Photoluminescence Properties In As-prepared Filmsmentioning
confidence: 84%
“…Indeed, the differences between the CPMAS and SPEMAS spectra increase for CG01 to CG04 samples, confirming that the molecular dynamics increases in the OLA moieties upon substitution. As already mentioned, this is mostly associated with the presence of motions in the intermediate regime time scale, which reduces the crosspolarization efficiency and interferes with the heteronuclear decoupling during the signal acquisition [30]. Therefore, this feature shows that for samples CG04, CG05 and CG06, the chitosan chains also become mobile at room temperature, so further increase in the OLA substitution do not significantly affect the overall dynamic behavior of the samples.…”
Section: Solid-state Nmr Analysismentioning
confidence: 86%
“…According to the Arrhenius law, the activation energy for the glass transition was calculated by fitting the frequency f versus 1/ T of the E″ (Figure ): lnf=lnf0EaRT f is the frequency (Hz), f 0 is the pre‐exponential factor (Hz), E a is the activation energy (J mol −1 ), T is the absolute temperature where the maximum of tan δ occurs for each relaxation process, and R is 8.32 J K −1 mol −1 . The calculated activation energy was approximately 595 kJ mol −1 .…”
Section: Resultsmentioning
confidence: 99%